Exploring perinatal mental health in Indonesia: A mixed-method study in Mataram, West Nusa Tenggara - Harahap, Ana P.; Adi, Mateus S.; Sriatmi, Ayun; Purnami, Cahya T. (Narra J, 2024)
A significant number of postpartum mothers are at risk of experiencing perinatal mental health (PMH) due to various factors. The aim of this study was to investigate risk factors for PMH issues and explore the current implementation of early screening for PMH in Mataram, West Nusa Tenggara, Indonesia. A mixed-method study, cross-sectional and ethnographic approach, was conducted at Babakan Public Health Center, Mataram, West Nusa Tenggara, Indonesia, from July to August 2023. A cross-sectional study involved 33 postpartum mothers and analyzed seven potential risk factors: age, parity, age at marriage, type of childbirth, type of family, history of adolescent mental disorder, and history of mental disorder during pregnancy. An ethnographic approach, using in-depth interviews, was utilized to gain insights regarding the implementation of PMH screening, included seven healthcare workers: six midwives and one nurse. Among the seven risk factors analyzed, only a history of adolescent mental disorder acted as risk for high PMH with an odds ratio (OR) 1.17 and p=0.03. In-depth interviews revealed a consistent lack of understanding among all healthcare workers regarding PMH screening implementation: absence of early screening, lack of knowledge regarding PMH and how to identify them, reliance solely on subjective assessments for early screening, and a lack of standardized adequate PMH management. In conclusion, the history of adolescent mental disorder could lead to the development of PMH in postpartum mothers. Current screening implementation is still lacking among healthcare workers and public health centers. Therefore, integrating various stakeholders in early PMH screening is crucial to prevent future PMH in mothers and babies.